Dipotassium Diaquadiphosphatooctaperoxotetramolybdate, [K2(P2O7){MoO(O2)2}2{MoO(O2)2(OH2)}2]2– – a One‐Dimensional Double Chain Array of Polyanions Linked by Potassium Cations1. Issue 10 (6th February 2013) - Aoki, Koji; Iwata, Keisuke; Iwata, Takahiro; Hashimoto, Masato
Abstract: A dipotassium diaquadiphosphatooctaperoxotetramolybdate, [K2 (P2 O7 ){MoO(O2 )2 }2 {MoO(O2 )2 (OH2 )}2 ] 2–, was crystallised as a tetramethylammonium salt and its structure was determined by single‐crystal X‐ray diffraction. The diaquadiphosphatooctaperoxotetramolybdate moiety (POPMo4) consists of four molybdenum decahedra and one μ4 ‐diphosphate group. All Mo atoms bear two peroxo groups at their equatorial positions. Two of the four Mo atoms are also coordinated by a water molecule. The four molybdenum decahedra are separated and linked by the diphosphate group. The POPMo4 moieties are linked by potassium atoms to form an infinite anionic 1D double chain. The chains are connected by hydrogen bonds to water of crystallisation molecules to form a 2D network. POPMo4 or its precursor gives a 31 P NMR signal at δ = –7.3 ppm in the reaction solution and is stable at low pH and a high Mo/diphosphate molar ratio. Abstract : A dipotassium diphosphatooctaperoxotetramolybdate was isolated as a tetramethylammonium salt. The diphosphatomolybdate moieties are linked by potassium atoms to form an infinite anionic 1D double chain. The chains are linked to each other by hydrogen bonds to water molecules to form a 2D network.